Evidence of Different IL-1β Activation Pathways in Innate Immune Cells From Indeterminate and Cardiac Patients With Chronic Chagas Disease - Medeiros, Nayara I.; Pinto, Bruna F.; Elói-Santos, Silvana M.; Teixeira-Carvalho, Andréa; Magalhães, Luísa M. D.; Dutra, Walderez O.; Correa-Oliveira, Rodrigo; Gomes, Juliana A. S. (Frontiers in Immunology, 2019)
Background: Chagas cardiomyopathy is the main fibrosing myocarditis among known heart diseases. Development of cardiomyopathy has been related to extracellular matrix (ECM) remodeling, wich are controlled by matrix metalloproteinases (MMPs) and cytokines, especially interleukin (IL)-1β. The convertion of 31KDa inactive precursor, the proIL-1β in 17KDa active IL-1β peptide, is controlled by caspase-1-dependent pathway, associated with inflammasomes. Other caspase-1 independent mechanisms mediated by proteases, especially as MMPs, have already been described. Methods: We evaluated IL-1β activation pathways in neutrophils and monocyte subsets from patients with different clinical forms of Chagas disease after T. cruzi antigen stimulation by multiparameter flow cytometry. Results: Our data demonstrated that Chagas patients with the indeterminate clinical form (IND) showed increased levels of IL-1β post-stimulation as well as increased expression of MMP-2, NLRP3, and CASP1, which are associated with the classical caspase-1-dependent pathway. Conversely, patients with the cardiac clinical form (CARD) showed increased IL-1β after stimulation associated with MMP-9 and alternative caspase-1-independent pathway. Conclusions: We suggest some distinct molecular mechanisms for production of IL-1 in innate immune cells from patients with different clinical forms of Chagas disease. MMP-2 and MMP-9 gelatinases are associated with distinct disease outcomes and IL-1 production.